Relevance of Country-Level Competitiveness Indexes in Asian Economies: A Critical Review - Das, Arindam; Kaul, Omkar (Asian Journal of Empirical Research, 2017)
This paper investigates popular country-level competitiveness indexes, analyzes their structural validity and assesses their ability to explain performance of economies and firms in key Asian economies. Time series cross correlation technique has been used to identify (a) presence of relationship between indexes, (b) presence of relationship between an index and macroeconomic performance of the country and (c) presence of relationship between an index and firm-level performance in the country. Analysis shows issues with the construct of indexes, presence of a large number of interdependent variables and significant presence of subjective data points collected through opinion polls, leading to a lack of robustness. It is also found that indexes do not correlate with each other in time series analysis. Indexes are able to explain macroeconomic performance of a nation, but they fail to relate to firm-level performance, suggesting reducing practical applicability of the indexes. Practitioners who utilize country-level competitiveness indexes for policy decisions or business decisions will be find the results insightful.